2021
DOI: 10.1002/ejoc.202100839
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Scale Synthesis of a Hexapeptide by Fragment Coupling in a Ball Mill

Abstract: Synthesis of long peptides is generally considered as being a challenge to peptide chemists, in addition to producing significant amounts of toxic waste, such as DMF. Here we show that using solvent-less methods, such as ball milling, enabled the production of the hexapeptide Boc-(Ala-Phe-Gly)2-OBn at the gram scale with high overall yield (77%, 5 linear steps). This is the longest peptide chain synthesized in a ball mill to date, in which the amino acid sequence is precisely controlled. This study complements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In response to these issues, Métro and co-workers [115] assessed the capacity of ball mills to reduce or eliminate the propensity for epimerization during the peptide coupling, comparing these results to those obtained with classical approaches in solution (Table 7). In addition, mechanosynthesis was developed using two different target amino acids: phenyl glycine (H-Phg-OH), known for its increased tendency for racemization, and isoleucine (H-Ile-OH), which has a significant…”
Section: Mechanochemical Formation Of Higher-ordered Peptide Structuresmentioning
confidence: 99%
“…In response to these issues, Métro and co-workers [115] assessed the capacity of ball mills to reduce or eliminate the propensity for epimerization during the peptide coupling, comparing these results to those obtained with classical approaches in solution (Table 7). In addition, mechanosynthesis was developed using two different target amino acids: phenyl glycine (H-Phg-OH), known for its increased tendency for racemization, and isoleucine (H-Ile-OH), which has a significant…”
Section: Mechanochemical Formation Of Higher-ordered Peptide Structuresmentioning
confidence: 99%
“…69 The risk of epimerization represents a severe hurdle in amide coupling. 70 In this regard, Métro and co-workers 71 examined the potential of ball milling to eliminate epimerization during peptide coupling. In the process, it was observed that the mechanochemical procedure required only one-third of this reaction time, probably as consequence of higher concentration of the reagents in the ball mill, that shortens reaction times relative to the corresponding reaction in solution.…”
Section: Amino Acid and Peptide Mechanosynthesismentioning
confidence: 99%
“…[34] In the context of small organic molecules chemistry, sustainable methods for the formation of amides are particularly required considering the high environmental impact of classical methods involving low atom economy activating agents such as HATU or EDCI. Greener approaches involving mechanochemistry, [35][36][37] neat reactions [38] or catalysis [39][40][41][42][43] have also been recently developed. The nature of the solvents used is also an important parameter and amide synthesis in water represents an alternative to highly toxic and hazardous solvents that are commonly used.…”
Section: Introductionmentioning
confidence: 99%